(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Ayurveda, the science of life, recognized lifestyle (Vihara) and diet (Ahara) as potential causes of disease. Childhood obesity in India is caused by factors such as altered lifestyle, food patterns, diet quality and quantity, increased physical inactivity, preserved junk foods, increased sedentary lifestyle, and more. The eight avoidable patients list (Ashtaunindit purushas) described by ancient Ayurvedic scholars includes the disease Sthaulya (obesity) along with the multi-channel approach of management, with the details of factors causing Sthaulya, pathophysiology (Samprapti), and treatment with exercise (Vyayam/Vihar), dietary (Ahar) interventions, remedies, and the body - purification/detoxification (Panchakarma) procedures. The importance of limiting/avoiding disease-causing factors, followed by medicinal management based on Dosha-Dhatu-Mala conditions, is described by ancient Ayurvedic scholars. This article examines the factors that contribute to childhood obesity using Ayurvedic principles.